Lenin : Genesis and Development of a Revolutionary - Theen, Rolf H. W., 1937- (Princeton legacy library., 2014)
This study shows how Lenin's life was permanently altered at the age of seventeen by the execution of his brother Alexander, his transformation from a model student in secondary school into a revolutionary at the university, his fascination with Chernyshevsky, and his long involvement with the Jacobin wing of the revolutionary movement.